ANALISIS KOMPARASI FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN BADAN USAHA MILIK DESA (BUMDes) DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Aprilina Ela; Garnasih Lestari Raden; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the comparative anlysis of the factors that affect the permormance of employees of BUMDes in Singingi Kuantan Singingi Regency. In this study there are 3 variables, namaley Innovation (X1), Sosial Capital (X2) and Employee permormance (Y). The population was employees of three BUMDes in Singingi. The sample of this research was 26 employees of BUMDes. The samples was carried out by using the total sampling technique method. To collet the data, this study used interview and questionnaires to the respondents. Meanwhile, in terms of data analysis, this study used descriptive, quantitative and comparative analysis, multiple regression to produce instrument test, classical assumptions and proving hypoyhesis testing, by using the SPSS program. The result showed that: 1). The three BUMDes of Singingi produced employees performance and innovation variables which have been implemented very well, and while the social capital have been implemented properly, there is also the performance of each BUMDes in Singingi District, where the variables are innovation, social capital, the highest permormance is in BUMDes Sejahtera Sungai Sirih Village, 2). The Variable thas has the most dominant influence on employee performance is the variable of innovation, 3). The application of employee permormance, innovation, and social capital has differences in the three BUMDes in Singingi.Keywords: Innovation, Sosial Capital, Employee Performance.